2006
DOI: 10.1007/s10620-006-9108-2
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Pantoprazole as Initial Treatment in Patients With Gastroesophageal Reflux Disease and a History of Erosive Esophagitis: A Randomized Clinical Trial

Abstract: We sought to evaluate safety and efficacy of IV pantoprazole when used as initial therapy in patients with gastroesophageal reflux disease (GERD) and a history of erosive esophagitis (EE) in a double-blind, placebo-controlled, randomized, parallel-group study. Patients were randomized to 7 days of once-daily IV or oral pantoprazole (40 mg) or placebo. Efficacy variables included maximal acid output, basal acid output, and changes from baseline in frequency/severity of GERD symptoms, and frequency of antacid us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Previous studies on intravenous infusion of pantoprazole have demonstrated its efficacy and safety in treating GERD [13], erosive esophagitis [14,15], Zollinger-Ellison syndrome [10], and acute gastrointestinal bleeding [11,12]. To our knowledge, our study is the first to show that intravenous infusion of pantoprazole, including infusion once a day or continuous infusion for 72 h, in treating severe esophagitis was efficient and safe.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Previous studies on intravenous infusion of pantoprazole have demonstrated its efficacy and safety in treating GERD [13], erosive esophagitis [14,15], Zollinger-Ellison syndrome [10], and acute gastrointestinal bleeding [11,12]. To our knowledge, our study is the first to show that intravenous infusion of pantoprazole, including infusion once a day or continuous infusion for 72 h, in treating severe esophagitis was efficient and safe.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, intravenous infusion produces a faster and steadier acid suppression than an does the oral regimen [10][11][12]. The safety of intravenous pantoprazole has been demonstrated in patients with GERD [13], with erosive esophagitis [14,15], with Zollinger-Ellison syndrome [10], or with bleeding ulcer [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Review outcome: The only study 39 comparing a PPI with placebo in patients with erosive esophagitis used intravenous pantoprazole and did not evaluate any of the clinical outcomes specified in this analysis. No studies comparing PPIs with H 2 -RAs or prokinetics for the healing of erosive esophagitis were published during the review period.…”
Section: Endoscopic Therapymentioning
confidence: 99%
“…Powered by TCPDF (www.tcpdf.org) pantoprazole include headache, nausea, dizziness, flushing, and pain at the site of injection; however, data on tolerability in this subset of patients are limited. 53 Randomized, controlled, double-blind control trials in patients with GERD have shown that oral pantoprazole 40 mg/day has a comparable tolerability profile to oral omeprazole 20 mg/day and lansoprazole 30 mg/day after 8 weeks of therapy. 54,55 In addition, oral pantoprazole 40 mg/day has similar tolerability comparing to H2RAs, such as ranitidine 300 mg/day and famotidine 40 mg/day.…”
Section: Safety and Tolerability Of Pantoprazolementioning
confidence: 99%